Haiti : challenges development assistance : conference report - Erikson, Daniel P. (Inter-American Dialogue WashingtonUS, 2002)
Addresses four themes viz. Haiti's political context; economic and social challenges; the status of current development assistance efforts; and, the role of the multilateral organizations in Haiti's economic development.